Pengaruh Budaya Sekolah dan Motivasi Kerja Terhadap Kinerja Guru di Gugus Bougenvile 4 Kecamatan Ulubelu - Hanafi, Asrofi Huda; Mu'in, Juhri Abdul; Siswoyo, Siswoyo; Hendrowati, Tri Yuni (Paedagogie, 2026)
This study aims to analyze the influence of school culture and work motivation on teacher performance in the Bougenvile 4 Cluster, Ulu Belu District. This research employed a quantitative approach using a survey method. The population consisted of all elementary school teachers within the Bougenvile 4 Cluster, and the sampling technique used was total sampling. Data were collected through a closed-ended questionnaire that had been tested for validity and reliability. Data analysis was conducted using descriptive and inferential statistics with the assistance of SPSS version 25, including prerequisite tests, simple linear regression, and multiple linear regression analysis. The results indicate that: (1) school culture has a positive and significant effect on teacher performance; (2) work motivation has a positive and significant effect on teacher performance; and (3) school culture and work motivation simultaneously have a positive and significant effect on teacher performance. The Adjusted R Square value of 0.701 indicates that 70.1% of the variation in teacher performance can be explained by school culture and work motivation, while the remaining percentage is influenced by other factors outside the scope of this study. These findings imply that improving teacher performance can be effectively achieved through strengthening a conducive school culture and enhancing teachers’ work motivation in a sustainable manner.